Respiratory Sinus Arrhythmia as an Index of Cardiac Vagal Control in Mitral Valve Prolapse - Bona Olexova, L; Sekaninova, N; Jurko, A; Visnovcova, Z; Grendar, M; Jurko, T; Tonhajzerova, I (Physiological research, 2020)
Respiratory sinus arrhythmia (RSA), i.e. heart rate (HR) variations during inspiration and expiration, is considered as a noninvasive index of cardiac vagal control. Mitral valve prolapse (MVP) could be associated with increased cardiovascular risk; however, the studies are rare particularly at adolescent age. Therefore, we aimed to study cardiac vagal control indexed by RSA in adolescent patients suffering from MVP using short-term heart rate variability (HRV) analysis. We examined 12 adolescents (girls) with MVP (age 15.9±0.5 years) and 12 age and gender matched controls. Resting ECG was continuously recorded during 5 minutes. Evaluated HRV indices were RR interval (ms), rMSSD (ms), pNN50 (%), log HF (ms(2)), peak HF (Hz) and respiratory rate (breaths/min). RR interval was significantly shortened in MVP group compared to controls (p=0.004). HRV parameters-rMSSD, pNN50 and log HF were significantly lower in MVP compared to controls (p=0.017, p=0.014, p= 0.015 respectively). Our study revealed reduced RSA magnitude indicating impaired cardiac vagal control in MVP already at adolescent age that could be crucial for early diagnosis of cardiovascular risk in MVP.
Keywords: Humans; srdeční frekvence; Mitral Valve Prolapse; Body Mass Index; Electrocardiography; Adolescent; Respiratory Sinus Arrhythmia; Vagus Nerve; nervus vagus; ženské pohlaví; mladiství; respirační sinusová arytmie; prolaps mitrální chlopně; index tělesné hmotnosti; Female; Heart Rate; lidé; elektrokardiografie